Rapid Accretion State Transitions following the Tidal Disruption Event AT2018fyk - Wevers, T.; Pasham, D.R.; Van Velzen, S.; Miller-Jones, James; Uttley, P.; Gendreau, K.C.; Remillard, R.; Arzoumanian, Z.; Löwenstein, M.; Chiti, A. (IOP Publishing Ltd, 2021)
Following a tidal disruption event (TDE), the accretion rate can evolve from quiescent to near-Eddington levels and back over timescales of months to years. This provides a unique opportunity to study the formation and evolution of the accretion flow around supermassive black holes (SMBHs). We present 2 yr of multiwavelength monitoring observations of the TDE AT2018fyk at X-ray, UV, optical, and radio wavelengths. We identify three distinct accretion states and two state transitions between them. These appear remarkably similar to the behavior of stellar-mass black holes in outburst. The X-ray spectral properties show a transition from a soft (thermal-dominated) to a hard (power-law-dominated) spectral state around L bol ∼ few × 10-2 L Edd and the strengthening of the corona over time ∼100-200 days after the UV/optical peak. Contemporaneously, the spectral energy distribution (in particular, the UV to X-ray spectral slope α ox) shows a pronounced softening as the outburst progresses. The X-ray timing properties also show a marked change, initially dominated by variability at long (>day) timescales, while a high-frequency (∼10-3 Hz) component emerges after the transition into the hard state. At late times (∼500 days after peak), a second accretion state transition occurs, from the hard into the quiescent state, as identified by the sudden collapse of the bolometric (X-ray+UV) emission to levels below 10-3.4 L Edd. Our findings illustrate that TDEs can be used to study the scale (in)variance of accretion processes in individual SMBHs. Consequently, they provide a new avenue to study accretion states over seven orders of magnitude in black hole mass, removing limitations inherent to commonly used ensemble studies.